1876 Ala. Code 929-30 - (:unkn) unknown (My University, 1871)
§ 4406: Prohibited hunting wild hogs with a dog and gun without giving notice to "at least three freeholders in the neighborhood." Violators fined not less than ten nor more than one hundred dollars.
Keywords: HUNTING REGULATION